Chameleons, red herrings, and false localizing signs in neurocritical care. (4th May 2022) - Li, Boyi; Sursal, Tolga; Bowers, Christian; Cole, Chad; Gandhi, Chirag; Schmidt, Meic; Mayer, Stephan; Al-Mufti, Fawaz
Abstract: False localizing signs (FLS) and other misleading neurological signs have long been an intractable aspect of neurocritical care. Because they suggest an incorrect location or etiology of the pathological lesion, they have often led to misdiagnosis and mismanagement of the patient. Here, we reviewed the existing literature to provide an updated, comprehensive descriptive review of these difficult to diagnose signs in neurocritical care. For each sign presented, we discuss the non-false localizing presentation of symptoms, the common FLS or misleading presentation, etiology/pathogenesis of the sign, and diagnosis, as well as any other clinically relevant considerations. Within cranial neuropathies, we cover cranial nerves III, IV, V, VI, VII, VIII, as well as multiple cranial nerve involvement of IX, X, and XII. FLS ophthalmologic symptoms indicate diagnostically challenging neurological deficits, and here we discuss downbeat nystagmus, ping-pong-gaze, one-and-a-half syndrome, and wall-eyed bilateral nuclear ophthalmoplegia (WEBINO). Cranial herniation syndromes are integral to any discussion of FLS and here we cover Kernohan's notch phenomenon, pseudo-Dandy Walker malformation, and uncal herniation. FLS in the spinal cord have also been relatively well documented, but in addition to compressive lesions, we also discuss newer findings in radiculopathy and disc herniation. Finally, pulmonary syndromes may sometimes be overlooked in discussions of neurological signs but are critically important to recognize and manage in neurocritical care, and here we discuss Cheyne-Stokes respiration, cluster breathing, central neurogenic hyperventilation, ataxic breathing, Ondine's curse, and hypercapnia. Though some of these signs may be rare, the framework for diagnosing and treating them must continue to evolve with our growing understanding of their etiology and varied presentations.